Perception of agricultural extension as a career among postgraduate students of agriculture in selected universities in South-West, Nigeria (2013)
The study investigated perception of agricultural extension as a career among postgraduate agricultural students in selected universities in south-west, Nigeria. Multi-stage sapling technique was used to select 171 respondents across three universities. Data were analyzed using both descriptive and inferential statistics (Chi-square, PPMC) at p=0.05. Majority were males (66.3%), Christians (81.7%) and single (73.5%) with mean age and mean formal years of education at 29.6 and 18.7 years, respectively. Lecture/classroom (67.3%) was the most important information source on agricultural extension, while similarity of course of study to personal and professional interest (mean=1.56) was the most paramount reason for the choice of present course of study. Majority (63.2%) possessed high knowledge of agricultural extension as a career, while 50.9% had a favourable perception towards the subject. Poor awareness of the potential careers in the discipline (77.1%), inadequate number of extension career resource centres (64.5%) and inadequate funding of agriculture (89.9%) were the major constraints facing respondents. Department (χ2=15.184), self-esteem of career in course of study (r=0.217) and constraints to agricultural extension (r=-0.174) were significantly related to respondents’ perception of agricultural extension as a career. Respondents are knowledgeable that agricultural extension has many career opportunities and someone with a career in the discipline will be competitive in the job market. However, they have some constraints crucial to their perception of the subject. Thus, efforts should be made by various stakeholders to address these constraints in order to improve respondents’ perception towards the discipline.